2005
DOI: 10.1016/j.neuron.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression by Lithium and Depletion of Inositol in Slices of Adult Rat Cortex

Abstract: of action of lithium in BD, and these have been re-Sethu Sankaranarayanan, 1 Adam J. Simon, 1 viewed (Gould et al., 2004; Gurvich and Klein, 2002). and Edward M. Scolnick 3 Glycogen synthase kinase 3 (GSK3) and inositol mono-1 Merck & Co., Inc. phosphatase (IMPase) are both inhibited by lithium and West Point, Pennsylvania 19486 have been topics of considerable study as potential 2 Rosetta Inpharmatics LLC, a wholly owned therapeutic targets in BD. subsidiary of Merck & Co. Inc. An effect of lithium on brain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 49 publications
8
55
0
Order By: Relevance
“…Alternatively, high lithium levels may be selectively toxic to newborn adult neurons, possibly through its known inhibition of enzymes critical to energy metabolism and nucleoside processing. 15,16,44 This would be consistent with the general finding that adult neurons are more susceptible to both toxic and energy deprivationtype insults than either adult glia or embryonic neurons.…”
Section: Discussionsupporting
confidence: 88%
“…Alternatively, high lithium levels may be selectively toxic to newborn adult neurons, possibly through its known inhibition of enzymes critical to energy metabolism and nucleoside processing. 15,16,44 This would be consistent with the general finding that adult neurons are more susceptible to both toxic and energy deprivationtype insults than either adult glia or embryonic neurons.…”
Section: Discussionsupporting
confidence: 88%
“…[6][7][8][9][10] Several pharmacogenomic studies investigating mood-regulating drugs have shown altered expression in several components of the BH 4 pathway. [11][12][13] Together, this evidence supports a link between the BH 4 pathway and mood control, as well as in antidepressant function. Because BH 4 is essential for such important biological systems, the regulation of the enzyme which is rate limiting for BH 4 synthesis, GTP cyclohydrolase I (GTPCH; Figure 1), could be biologically, pathologically and therapeutically important.…”
Section: Introductionsupporting
confidence: 61%
“…Lithium inhibits inositol monophosphatase and downstream GSK3beta at therapeutically effective concentrations, and it has been hypothesized that depletion of brain inositol levels is an important neurochemical change forming the molecular basis of lithium's therapeutic efficacy in bipolar disorder. 106 GPR88 is upregulated by methamphetamine and valproate, a clinically effective drug in treatment of bipolar disorders, in mouse pharmacogenomic models for bipolar disorders. 37 GPR88 expression on the transcriptional level is lower in BDNF-deficient mice.…”
Section: Number Of Transcripts Affected By Single and Multiple Treatmmentioning
confidence: 99%